(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
After we have considered the general nature of the linguistic problems of informatics, their composition, origin, structure and prospects, it becomes clear that specific problems depend on the type of linguistic unit supplied to the computer input. In our consideration, we will adhere to the principle of succession from the smallest linguistic unit to the largest: from phoneme, grapheme, morpheme to word form, word, phrase, statement, sentence, text as a whole. Linguistics issues and methods and applications are discussed in Computational Linguistics.